Analisis Kelayakan Investasi Pada Saham-Saham Perusahaan Manufaktur Sub Sektor Food And Beverages Yang Terdaftar Di BEI Periode 2017-2019 - Oktaviani, Leni; Ali, Karnila (Universitas Muhammadiyah Metro, 2022)
The objectives of this research are: (1) To determine the stock return and risk by using the Capital Asset Pricing Model (CAPM) method in determining investment decisions in stocks of the food and beverages sub-sector for the period 2017-2019 and (2) to determine the feasibility level of shares of issuers in the food and beverages sub-sector listed on the IDX for the 2017-2019 period. The sampling technique used is purposive sampling, which is a sampling technique with certain considerations. So that the selected sample of 13 companies. The results of this study indicate that: (1) Based on the results of data analysis there is a non-linear relationship between systematic risk (Beta) and the expected rate of return (E(Ri)). Example: CEKA stock has the highest beta of 1.113 and has the lowest E(Ri) of 0.00020268. (2) There is 1 share that has the feasibility as an investment facility, namely CEKA shares. CEKA's shares have Ri greater than [E(Ri)] or [Ri > E(Ri)]. The investor's decision that must be taken by the investor is to buy the shares. Meanwhile, the 12 company shares that were included in the unqualified category were AISA, ALTO, CEKA, DLTA, ICBP, INDF, MLBI, MYOR, ROTI, SKBM, SKLT, STTP, and ULTJ shares. These stocks have Ri smaller than E(Ri) or [Ri < E(Ri)]. The investment decision that must be taken by investors is to sell the shares before the price drops.